Predictive control for trajectory tracking and decentralized navigation of multi-agent formations - Prodan, Ionela; Olaru, Sorin; Stoica, Cristina; Niculescu, Silviu-Iulian (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses a predictive control strategy for a particular class of multi-agent formations with a time-varying topology. The goal is to guarantee tracking capabilities with respect to a reference trajectory which is pre-specified for an agent designed as the leader. Then, the remaining agents, designed as followers, track the position and orientation of the leader.
Keywords: multi-agent systems; linear systems; model predictive control; potential function; polyhedral function